Electrochemically activated persulfate and peroxymonosulfate for furfural removal: optimization using Box–Behnken design. Issue 9 (16th April 2023) - Can-Güven, Emine; Ilhan, Fatih; Ulucan-Altuntas, Kubra; Yazici Guvenc, Senem; Varank, Gamze
ABSTRACT: Furfural removal by electrochemically activated peroxydisulfate (E-PS) and peroxymonosulfate (E-PMS) was investigated. The effect of different anodes was investigated for the electrochemical activation of oxidants. Box Behnken Design was applied to determine optimum operating conditions, which were determined as follows; PS concentration: 2.3 mM, applied current: 1.15 A, pH: 3.5, and reaction time: 118.3 min for E-PS process; PMS concentration: 1.8 mM, applied current: 1.05 A, pH: 3.3, and reaction time: 107.8 min for E-PMS process. The results of the study showed that the E-PMS process is more advantageous in terms of the chemical and electricity costs to be used. GRAPHICAL ABSTRACT: UF0001